THE INFLUENCE OF PARENTAL PATTERNS ON STUDENT LEARNING ACHIEVEMENT AT SMA NEGERI 10, KOTA TERNATE - Rahmatia A. Imam; Ariantje J. A. Sundah; Rinna Y. Kasenda (Prodi Bimbingan Konseling Universitas Negeri Manado, 2023)
Parenting patterns affect the way children develop, because families, especially parents, are the closest people to children who can shape children's behavior, personality and habits as well as education. Many children follow the behavior of their parents. Parenting patterns that are owned also greatly affect children's learning achievement and to achieve a goal this study aims to determine the effect of parenting parents on student achievement in SMA Negeri 10 Ternate City.This research is a quantitative research with a correlational method, by means of simple random sampling of 42 students of SMA Negeri 10 Kota Ternate in the academic year 2020/2021. Data were collected through a questionnaire with a Likert scale. The data analysis technique used simple linear regression analysis with the help of a computer program SPSS 23 for windows. The results showed that there was an effect of parenting style on student learning achievement obtained by the equation Y = 22.411 - 0.725 X with the ratio of the increase in the two variables quantitatively is 1: 0.725 this comparison shows that if there is an increase in the value of the parenting style variable ) then the level of increase in the value of the student achievement variable (Y) will be followed of 22.411. The regression equation is significant or will not be tested using the Fcount value at the significant level of 0.05. It means that Ha is accepted and Ho is rejected. The conclusion that the hypothesis that says there is an effect of parenting style on student achievement in SMA Negeri 10 Ternate City is accepted and significant, this is indicated by the regression coefficient value (F) 4.050 with a significant 0.000.